Isolasi steroid dari daun beluntas (Pluchea Indica l.) menggunakan metode sonikasi - Mubarokah, Maulida Filailin (Maliki Interdisciplinary Journal, 2024)
Beluntas plant (Pluchea indica L.) is one plant that contains several compounds such as alkaloids, steroids, tannins, essential oils, and phosphorus. Steroids are important bioactive molecules that have a basic skeleton consisting of 17 carbon atoms arranged in 4 joined rings, among which there are 3 cyclohexane and cyclopentane rings. This experiment was carried out with the aim of isolating steroid compounds, separating using preparative thin-layer chromatography (KLTP) techniques, and identifying steroid isolation results using UV-Vis and FTIR (Fourier Transform Infrared) spectrophotometer instruments. The method used for isolation is the sonication method. This method uses ultrasonic waves to break up cell walls so that the steroid content can come out easily. This method was chosen because the insulation process is fast, inexpensive, and produces high yields. The results of isolation of steroid compounds from beluntas leaves using this sonication method resulted in as much as 9,714 g of compounds with a yield of 32.38%. Separation using KLTP showed an Rf value of steroid compounds of 0.92. This steroid compound can be recognized by a change in color to dark purple or dark green when irradiated using UV light. However, from the results of characterization using UV-Vis did not obtain the typical absorption spectrum of steroid compounds due to the steroid content in the sample is too little.